Systems biology approach reveals a link between mTORC1 and G2/M DNA damage checkpoint recovery - Hui-Ju Hsieh (Nature Portfolio, 2018)
DNA damage induces checkpoints to ensure that damage is not transferred to the next generation, but the molecular pathways responsible for checkpoint recovery are not clear. Here the authors show that the nutrient sensor mTORC1 is a determinant for G2/M checkpoint recovery through regulation of cyclin B1 and PLK1 expression.